Combination Chemotherapy using L-Asparaginase, Daunorubicin, and Cytosine Arabinoside in Adults with Acute Myelogenous Leukaemia. Issue 5734 (28th November 1970) - Crowther, D.; Bateman, C. J. T.; Vartan, C. P.; Whitehouse, J. M. A.; Malpas, J. S.; Fairley, G. Hamilton; Scott, Ronald Bodley
Abstract : Cytosine arabinoside and daunorubicin used in an intensive intermittent regimen have been shown to be an effective combination for the induction of complete remissions in 14 out of 23 adult patients with acute myelogenous leukaemia. This gives an overall complete remission rate of 60%. A further patient had a good partial remission. The addition of L-asparaginase to the regimen has not increased the incidence of remission and there were more side effects in the L-asparaginasetreated group. Of the 10 patients treated with L-asparaginase in addition to cytosine arabinoside and daunorubicin, five achieved a complete remission. Of the 13 patients treated with cytosine arabinoside and daunorubicin without L-asparaginase, nine achieved a complete remission and one a good partial remission.